2007
DOI: 10.1016/j.jmr.2006.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity enhancement by exchange mediated magnetization transfer of the xenon biosensor signal

Abstract: Hyperpolarized xenon associated with ligand derivitized cryptophane-A cages has been developed as a NMR based biosensor. To optimize the detection sensitivity we describe use of xenon exchange between the caged and bulk dissolved xenon as an effective signal amplifier. This approach, somewhat analogous to 'remote detection' described recently, uses the chemical exchange to repeatedly transfer spectroscopic information from caged to bulk xenon, effectively integrating the caged signal. After an optimized integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…Several studies reported CEST imaging of biological molecules such as glycogen,68 an endogenous lysine-rich protein (LRP) as a reporter gene,69 and proteins and peptides 70. CEST imaging was also applied to MRI of a hyperpolarized Xe noble gas 71, 72. These CEST probes are classified as DIACEST because of their diamagnetic nature 73…”
Section: Multifunctional Nanomedicinementioning
confidence: 99%
“…Several studies reported CEST imaging of biological molecules such as glycogen,68 an endogenous lysine-rich protein (LRP) as a reporter gene,69 and proteins and peptides 70. CEST imaging was also applied to MRI of a hyperpolarized Xe noble gas 71, 72. These CEST probes are classified as DIACEST because of their diamagnetic nature 73…”
Section: Multifunctional Nanomedicinementioning
confidence: 99%
“…While detecting a reduction in water signal produced by saturation pulse(s) is still the predominant method for observing CEST contrast, several alternative methods have been also reported (73-77), and more may be presented in the near future. Therefore, to be more general, CEST is defined as a type of MRI contrast that is created by applying pulses to exchangeable protons and observing the subsequent alteration in water magnetization.…”
Section: Introductionmentioning
confidence: 99%
“…The FLEX and Exchange Signal Averaging (ESA) sequences are fundamentally different from saturation transfer in that a modulation in water signal is imparted based on an evolution time (t evol ) which is similar to the indirect dimensions in multi-dimensional NMR experiments (73,77,100). These methods aren't technically CEST methods, as saturation transfer is not employed, however they fall under the CEST imaging umbrella as they are methods which allow the collection of images with the contrast in these images dependent on chemical exchange.…”
Section: Introductionmentioning
confidence: 99%
“…In the direct detection methods, fast repetition of spectrallyselective pulses around the small reservoir resonance frequency (and detection after each pulse) uses the chemical exchange between the two environments to gradually increase the signal-to-noise ratio. 56,57 The repetition rhythm is chosen according to the exchange rate of xenon between the two environments.…”
Section: Methodsmentioning
confidence: 99%